2006
DOI: 10.1615/critrevbiomedeng.v34.i6.30
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Therapy, Part 2: Hyperthermia Techniques

Abstract: Hyperthermia, the procedure of raising the temperature of a part of or the whole body above normal for a defined period of time, is applied alone or as an adjunctive with various established cancer treatment modalities such as radiotherapy and chemotherapy. Clinical hyperthermia falls into three broad categories, namely, (1) localized hyperthermia, (2) regional hyperthermia, and (3) whole-body hyperthermia (WBH). Because of the various problems associated with each type of treatment, different heating techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
147
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(149 citation statements)
references
References 311 publications
(307 reference statements)
2
147
0
Order By: Relevance
“…[15a] In our particular case, this means that even at lower 808 nm laser intensities the temperature at the injection site could reach temperatures of 50 ºC and higher, as required for tumor ablation. [28] It should be noted at this point that the 808 nm power density here used (0.6 W·cm -2 ) is well below the power densities previously used in photothermal therapies of cancer tumors also based on neodymium-doped NPs (typically above 1 W·cm -2 ) where a nonnegligible heating of non-targeted tissues was evidenced. [4b, 29] Indeed, such a low irradiation intensity is comparable to that previously used during the minimally invasive photothermal therapies of cancer tumors based on carbon nanostructures.…”
Section: Spectroscopic Characterizationmentioning
confidence: 88%
See 1 more Smart Citation
“…[15a] In our particular case, this means that even at lower 808 nm laser intensities the temperature at the injection site could reach temperatures of 50 ºC and higher, as required for tumor ablation. [28] It should be noted at this point that the 808 nm power density here used (0.6 W·cm -2 ) is well below the power densities previously used in photothermal therapies of cancer tumors also based on neodymium-doped NPs (typically above 1 W·cm -2 ) where a nonnegligible heating of non-targeted tissues was evidenced. [4b, 29] Indeed, such a low irradiation intensity is comparable to that previously used during the minimally invasive photothermal therapies of cancer tumors based on carbon nanostructures.…”
Section: Spectroscopic Characterizationmentioning
confidence: 88%
“…[1] In order to maximize the efficacy of the therapy and to simultaneously minimize the undesirable collateral damage, the tumor must be heated up to cytotoxic levels while keeping the heating at the surroundings at a minimum. [2] Such selectivity has been achieved by using photothermal nanoparticles (PT-NPs), capable of efficient heat generation under optical excitation. Nanoparticle-assisted photothermal therapy (NP-PTT) consists on the selective incorporation of heating NPs inside the tumor to be treated in such a way that a subsequent optical excitation would produce a well localized heating of the tumor.…”
Section: Introductionmentioning
confidence: 99%
“…1 It is being applied, alone or in combination with other therapeutic procedures, as an alternative treatment for several diseases, including cancer. When tumor cells undergone a hyperthermia treatment, the net effects caused on them are strongly dependent on both the magnitude of heating and treatment duration.…”
mentioning
confidence: 99%
“…Miyata and Tei [69] examined the chronic effects of repeated Waon therapy on HF and found that four weeks of Waon therapy significantly improved symptoms, increased the ejection fraction (EF), and decreased the cardiac size on both the echocardiogram and chest X-ray. They also found that daily Waon therapy for two weeks decreased ventricular premature contractions and increased heart rate variability in patients with HF, implying that Waon therapy improved ventricular arrhythmias.…”
Section: Waon Therapymentioning
confidence: 99%
“…Short-waved diathermy applicators employ either a two-condenserplate system or an inductioncoil system. The heating can be targeted by positioning the applicator on the human body correctly [69]. When RF radiation interacts with matter, it can be absorbed, transferring the energy to the medium.…”
Section: Diathermymentioning
confidence: 99%